THE SECOND VATICAN COUNCIL - Melloni, Alberto (Asian Horizons, 2012)
The Second Vatican Council was announced by John XXIII on 25 January 1959 in the sacristy of St. Paul’s Outside the Walls during the concluding liturgy of the week of prayer for Christian unity.